Systemic Inflammatory Response Syndrome After Administration of Unmodified T Lymphocytes - Papadopoulou, Anastasia; Krance, Robert A; Allen, Carl E; Lee, Daniel; Rooney, Cliona M; Brenner, Malcolm K; Leen, Ann M; Heslop, Helen E (Molecular therapy, 2014)
Systemic inflammatory response syndrome (SIRS) is a rare systemic inflammatory response associated with fever, tachycardia, profound hypotension, and respiratory distress, which has been reported in cancer patients receiving T cells genetically modified with chimeric antigen receptors to retarget their specificity to tumor-associated antigens. The syndrome usually occurs following significant in vivo expansion of the infused cells and has been associated with tumor destruction/lysis. Analysis of patient plasma has shown elevated cytokine levels, and resolution of symptoms has been reported after administration of steroids and/or antibodies (such as anti–tumor necrosis factor and anti-interleukin (IL)-6 receptor antibodies) that interfere with cytokine responses. To date, SIRS has not been reported in subjects receiving genetically unmodified T cells with native receptors directed against tumor antigens, in which greater physiological control of T-cell activation and expansion may occur. Here, however, we report a patient with bulky refractory Epstein-Barr virus (EBV)–associated lymphoma, who developed this syndrome 2 weeks after receiving T cells directed against EBV antigens through their native receptors. She was treated with steroids and etanercept, with rapid resolution of symptoms. SIRS may therefore occur even when T cells recognize antigens physiologically through their “wild-type” native receptors and should be acknowledged as a potential complication of this therapy.